Contrasting tillage systems and vertical arable layer stratification impacts on soil aggregates and root biomass in Lithuania - Inga Andruškaité; Vaclovas Bogužas (Research in Agricultural Engineering, 2023)
Tillage intensity can affect soil quality through soil aggregates, which are strongly associated with organic carbon. In this study, we evaluated the effect of different intensity tillage (conventional ploughing (CP), shallow ploughing (SP), deep cultivation (DC), shallow cultivation (SC), no-tillage (NT)) on soil organic carbon (SOC) and soil aggregates at the 0-5, 5-10, 10-20 and 20-30 cm layers and root biomass at the 0-10, 10-20 and 20-30 cm layers. The field experiment on spring barley (Hordeum vulgare L.) consisted of a split-plot arrangement with four replications. Dry soil aggregates were evaluated using the mean weight diameter (MWD) index. Wet aggregates were assessed using a water-stable aggregate (WSA) index. We identified that tillage intensity significantly influenced the MWD index at four soil levels. Shallow tillage showed greater results at 0-5 and 5-10 cm depths. However, deep tillage increased the MWD at 10-20 and 20-30 cm depth. NT was dominated by evaluating the WSA at every level of the soil. SOC was correlated with WSA. The highest SOC was found under NT. The different tillage intensities did not significantly affect root biomass.